2018
DOI: 10.1016/j.dib.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Experimental datasets on engineering properties of expansive soil treated with common salt

Abstract: Construction of highway pavements or high rise structures over the expansive soils are always problematic due to failures of volume change or swelling characteristic experienced in the water permeability of the soil. The data in this article represented summary of (Durotoye et al., 2016; Durotoye, 2016) [1], [2]. The data explored different percentages of sodium chloride as additive in stabilizing the engineering properties of expansive soil compared with other available stabilizer previously worked on. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Meanwhile, (PSP) liquid limit dropped at 4 and 6 %, plastic limit dropped at 10 % and plasticity index at 6 % respectively. The finding of the study is similar to that of [27]. Table 3 and figure 3 showed that the maximum dry densities of the lateritic soil increases as the percentages of the stabilization agent increases, however at 6%, Periwinkle Shell Powder reached the peak MDD as further addition of 8% and 10% PSP led to a reduction in the soil MDD to 1892.46kg/m3 and 1867.80kg/m3 respectively.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Meanwhile, (PSP) liquid limit dropped at 4 and 6 %, plastic limit dropped at 10 % and plasticity index at 6 % respectively. The finding of the study is similar to that of [27]. Table 3 and figure 3 showed that the maximum dry densities of the lateritic soil increases as the percentages of the stabilization agent increases, however at 6%, Periwinkle Shell Powder reached the peak MDD as further addition of 8% and 10% PSP led to a reduction in the soil MDD to 1892.46kg/m3 and 1867.80kg/m3 respectively.…”
Section: Methodssupporting
confidence: 83%
“…However, in view of using a sustainable stabiliser that will be cost effective and eco-friendly [26][27] used common salt to stabilised expensive soil and noticed that the addition of 1.5 % of common salt to the weight of expansive soil decreased the swelling behaviour but improve the strength quality of expansive soil, thereby made the treated soil more stabilized.…”
Section: Introductionmentioning
confidence: 99%
“…These results were then compared with the minimum standards. The data presentation is similar to that of [1] , [21] , while safety procedures recommended in [22] , [23] , [24] were strictly followed in preparing the control samples.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 94%
“…The outcome of the strength test revealed the performance and standard of local building materials in low cost housing production [19] , [20] . The presentation of data is also similar to that of [21] , the experimental procedure of data presented took into consideration the recommendations of [22] , [23] , [24] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%